Morfološke značilnosti vrhunskih balinarjev - Čuk, Ivan (Šport (Ljubljana), 2016)
Bocce vole is a very old sport, and have following disciplines: bowling game, fast bowling, precision game and progression game. Bowlers are using bowls with a diameter between 90 mm. and 110 mm; and weight between 900 gr. and 1200 gr. Aim of our investigation was to determine basic morphologic characteristics of top level bowlers and if their body is symmetric. On the sample of 58 top level bowlers (average age of 38 years) who were attending World Championship in Kranj year 2001 we measured 15 anthropometric characteristics - joint diameters, circumferences and skinfold thicknesses on the left and right side. While there were no differences between the left and right diameters, there were significant differences between the left and right circumferences and skinfold thicknesses of thigh, upper arm and lowerarm. Despite low load during competitions and trainings after long period of time body adaptation is significant. It would be good for bowlers to perform compensation exercises to avoid health related problems e.g. scoliosis.
Keywords: anthropometrics; antropometrija; asimetrija; balinanje; bilateral differences; bocce vole; bowling; male; morfološke lastnosti; moški; sport; šport